Analisis SWOT dan Media Pembelajaran di Politeknik dalam Masa Covid-19 - Iis Mariam; Nidia Sofa; Nining Latianingsih; Endah Wartiningsih (Journal of Management and Business Review, 2021)
The purpose of this study is to find out and analyze how the media and  learning strategies carried out in the Covid-19 period of polytechnics using the SWOT analysis approach. The problem that occurs during Covid-19 in the learning process is not provided regulation about distance learnin, the selection of appropriate learning media and strategy  to help learners more easily understand the material being studied.The unit of analysis in this study is students in Business Administration-PNJ, sample selection using random sampling, data collection techniques using literature studies, observations and questionnaires. The method used in this research is a qualitative descriptive. The results showed that the learning media used were zoom meetings, e-learning and WhatsApp, and there were no rules that could be used as guidelines regarding the model set at PNJ for use in the distance learning proces. The results of this research used SWOT analysis for learning strategy are: (S): transportation costs are more efficient, easier to manage time management, have a lot of time to do campus work, access to learning can be done from anywhere, learning motivation increases, more relaxed and comfortable in the learning process, completing assignments from lecturers have enough tim,  more motivated, have their own planning work, increase, (W): not all lecturers use the zoom meeting or google classroom, learning process is not communicative, learning situation more different when the presentation uses online, (O) have learn more material from open source, live more healthy, no stress, more patient and happy learning arround the families, accustomed to online learning, accustomed to with information technology, (T) it takes time for discipline learning in the new normal era, lecturers must be more creative in teaching and learning, mastering of uisng  information technology.